Influencia de la ganadería en la comunidad de macroinvertebrados acuáticos en microcuencas de los Andes centrales de Colombia - Ramírez, Yuly Paulina (Universidad de Costa Rica, 2018)
Abstract: Influence of cattle ranching on the community of aquatic macroinvertebrates in watersheds of central Andes, Colombia. In order to measure the impact of cattle ranching and riparian corridors on the composition and diversity of benthic macroinvertebrates in Andean watersheds, nine headwater streams were selected in the municipality of Villamaría (Caldas, Colombia), five of them with riparian corridors and four without protection. In july (2013) in each stream, macroinvertebrate samples were collected using D and Surber nets, and streams were characterized according to water quality, channel metrics and habitat quality score. In total 98 934 individuals were collected, distributed in nine classes, 17 orders, 56 families and 92 genera. Veneroidea was the most abundant order followed by Trichoptera, Diptera, Tubificida and Ephemeroptera. Coleoptera was the order with highest richness with 28 genera, followed by Diptera with 18, Trichoptera with 11, Ephemeroptera with 10 and Odonata with 8. Streams with riparian corridors were deeper, had higher proportion of coarse substrates and Habitat Quality Score and presented higher genus diversity than those unprotected (p<0.05). The genera Ferrisia, Eurygerris, Heleobia and Pisidium, total nitrogen, ammonia nitrogen and silt proportion on the streambed were correlated with unprotected streams, whilst the genus Rhagovelia, the subfamily Chironominae, the Habitat Quality Score and the proportion of coarse substrates were correlated with streams with riparian corridors. This information confirms that riparian corridors help reducing the negative impact generated by cattle ranching practices and improve the provision of environmental services, and therefore it is recommended to maintain the strip of riparian vegetation in streams that possess it and allow the establishment of this in streams devoid of forest on its slopes.Key words: Watersheds, riparian corridors, benthos, water quality.